Anna Maria Wajda, Szkice z biblijnego zwierzyńca (Kraków: Petrus 2016) - Bąk, Tomasz Bartłomiej (Verbum Vitae, 2017)
Book review: Anna Maria Wajda, Szkice z biblijnego zwierzyńca (Kraków: Wydawnictwo Petrus, 2016). Ss. 317. PLN 39,00. ISBN 978-83-7720-214-2.